2022
DOI: 10.3892/etm.2022.11756
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inhaled β‑caryophyllene on vascular stiffness in smokers: A randomized, double‑blind, placebo‑controlled trial

Abstract: Approximately 1.14 billion smokers worldwide are at risk of developing tumors, cardiovascular diseases and respiratory diseases. Smoking cessation is the first choice of health care; however, the disease should be attenuated in individuals who never stop smoking, which escalates medical costs. Therefore, alternative options are needed to manage the social burden. The present study proposed an alternative method to prevent such diseases by inhalation of β-caryophyllene (BCP). A placebo-targeted, dose-searching,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…All the active compounds in the nebulized agent are naturally found in foods common in the diet, and each has established values for daily dietary intake. Each of the five active ingredients have individually undergone human clinical trials via the inhalation pathway and have demonstrated efficacy and safety in their use ( Prousky, 2007 ; Buhl et al, 1990 ; Holroyd et al, 1993 ; Calabrese et al, 2015 ; Homma et al, 2012 ; Bishop et al, 2005 ; Panahi et al, 2023 ; Li et al, 2018 ; Yamada et al, 2023 ; Williams, 2013 ; Smith et al, 1952 ; Kim et al, 2014 ; Jager et al, 1996 ). At present, the nebulized antioxidant/anti-pathogen agent is manufactured as a compounded medicine exclusively for a single complementary medicine center (Salerno Center, New York) and is not available through any other source.…”
Section: Methodsmentioning
confidence: 99%
“…All the active compounds in the nebulized agent are naturally found in foods common in the diet, and each has established values for daily dietary intake. Each of the five active ingredients have individually undergone human clinical trials via the inhalation pathway and have demonstrated efficacy and safety in their use ( Prousky, 2007 ; Buhl et al, 1990 ; Holroyd et al, 1993 ; Calabrese et al, 2015 ; Homma et al, 2012 ; Bishop et al, 2005 ; Panahi et al, 2023 ; Li et al, 2018 ; Yamada et al, 2023 ; Williams, 2013 ; Smith et al, 1952 ; Kim et al, 2014 ; Jager et al, 1996 ). At present, the nebulized antioxidant/anti-pathogen agent is manufactured as a compounded medicine exclusively for a single complementary medicine center (Salerno Center, New York) and is not available through any other source.…”
Section: Methodsmentioning
confidence: 99%
“…The beneficial effect of BCP was noted to be via inhibition of the TLR4/MyD88/NF-κB signaling pathway and direct activation of CB 2 R [69,105]. Interestingly, in a clinical trial with smokers, it was shown that a 12-week BCP intervention (performed using a flavor capsule inserted into the cigarette filter) caused a reduction in brachial-ankle pulse wave velocity (an indicator of arterial sclerosis) but had no effect on blood pressure parameters (e.g., DBP, SBP, pulse pressure, heart rate and ankle brachial index) [192]. In male normotensive Wistar rats, an intravenous bolus dose of α-pinene or β-pinene caused transitory hypotension and tachycardia, which was hypothesized to be suggestive of a pronounced drop in vascular resistance and subsequent compensatory sympathetic peripheral vasoconstriction induced by activation of the baroreflex [193].…”
Section: Anti-hypertensive Effects Of Taurine and Terpenesmentioning
confidence: 99%